Peran Guru dalam Membentuk Karakter Disiplin Santri di TPQ Nurul Hikmah Desa Argoyuwono Kecamatan Ampelgading - Moch. Fatchur Rozi; Luqman Hakim (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the role of teachers in shaping the discipline character of students at the Nurul Hikmah Al-Qur'an Education Park (TPQ), Argoyuwono Village, Ampelgading District. Using a descriptive qualitative approach, data was obtained through observation, in-depth interviews, and documentation of teachers, students, parents, and community leaders. The results of the study show that teachers play the role of educators, role models, guides, motivators, and facilitators in shaping the character of student discipline. The strategies implemented include habituation, example, and reinforcement that are carried out consistently. Supporting factors for the formation of discipline include family support, community leaders, and village mutual cooperation culture. Meanwhile, inhibiting factors include limited learning time, supervision intensity, as well as the family background and socioeconomic conditions of students. This research emphasizes the importance of synergy between teachers, families, and the community in shaping the character of student discipline in the non-formal Islamic education environment, especially in rural areas.